Increases in jump-and-reach height through an external focus of attention - Wulf, G.; Zachry, T.; Granados, C.; Dufek, J. S. (International Journal of Sports Science and Coaching, 2007)
The present study examined whether the previously observed benefits of an external focus of attention (i.e., focusing on the movement effect), relative to an internal focus (i.e., focusing on one's body movements) and control conditions, would generalize to tasks requiring maximum force production, such as jumping. In two experiments, participants performed a vertical jump-and-reach task. A Vertec™ measurement device was used to determine jump-and-reach height. Participants performed under three conditions in a within-participant design: External focus (i.e., focus on the rungs of the Vertec that were to be touched), internal focus (i.e., focus on the finger, with which the rungs were to be touched), and control conditions (i.e., focus on jumping as high as possible). Experiment 1 showed that participants' jump-and-reach height was greatest with an external focus. Those results were replicated in Experiment 2. In addition, it was observed that the vertical displacement of the center of mass was greater under the external focus condition, compared to the other two conditions. This suggests that participants jumped higher by producing greater forces when they adopted an external focus. These findings indicate that the previously shown benefits of an external attentional focus generalize to tasks requiring maximal force production.